Descriptive Study of Cadre Knowledge About Filling in KMS at Simpang Baru Health Center Pekanbaru - Helma Riana; Musfardi Rustam (Universitas Islam Negeri Alauddin Makassar, 2022)
Posyandu activity one of the activities is to monitor the growth of children under five through KMS. Based on data from the Pekanbaru City Health Office, it is known that the highest number of cadres is in the Simpang Baru Pekanbaru Health Center. The purpose of this study was to Determine The Knowledge Of Cadres About Filling KMS Toddlers in Puskesmas Simpang Baru Pekanbaru Years 2015. This research uses quantitative research. Based on the description of the results of research on cadre knowledge about KMS in the Simpang Baru Pekanbaru Puskesmas in 2015, the researcher can conclude that the majority of respondents lack knowledge about KMS as many as 31 people (68.9%). The research sub-variables can be identified as follows: the majority of respondents lack knowledge about KMS by 25 people (55.6%), lack knowledge about the causes of hypertension by 21 people (46.7%), and lack knowledge about how to fill KMS by 27 people (60.0%).